PENDEKATAN TRANSKULTURAL DALAM PELAYANAN KESEHATAN GIGI - Budiharto Budiharto (Faculty of Dentistry, Universitas Indonesia, 2015)
In developing professionalism dental health services for patient, which it uses the transculture approach as a theory foundation in giving dental professional guidance. It is hope that the fifth of subsystems inside professional values, relationships between professional, management approach, decision making system and dental health care method will be success. Transcultural dental health services is implemented in accordance with the backgroun of patient's culture thereby possibly allowing the acceptable treatment an care in accordance with is desired.